Affixation of Taro Dialect: A Descriptive Study - Kadek Artawan (Universitas Pendidikan Ganesha, 2018)
This descriptive study aimed at describing the number of prefixes and suffixes in Taro Dialect and its types of inflectional and derivational. This study is a descriptive qualitative research. Two informant samples of Taro Dialect were chosen based on a set of criteria. The data were collected based on three techniques, namely; observation, recording technique, and interview (listening and noting) technique. The results of the study show that there were five prefixes and five suffixes existing in Taro Dialect. The prefixes were N-, ma-, sa-, pa-, and ka-. The suffixes were -in, -ne, -an, -ang, and -e. The prefixes and suffixes that belong to derivation are: prefix N-, ma-, sa-, pa, and ka- and suffix -ang, an, -ne, and -in. The prefixes and suffixes that belong to inflection are: prefixes N-, ma-, and ka- and suffix -ang, an, -ne, -in, and -e.